(3GdeSFhdjI GdeOfjI Yf CYeGd gjFGJ GdEPGYI (B: s (3OQGSI ebGQfI (B/ s - (3GdTjeGA UdGM eMehO Ydis; (3eMeO SGei YHOGdUGOb s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2020)
(3LGAJ GdQSGdI JMJ Yfhf GdeSFhdjI GdeOfjI Yf CYeGd gjFGJ GdEPGYI (B- (3OQGSI ebGQfI(B: (3h dHjGf gPg GdeSFhdjI cGf dG HO ef GdJYQV ChkdG dJMOjO GdebUhO HgjFGJ GdEPGYI bGfhkfG(B: (3ceG YQagG GdeTQY ai GdbGfhf Qbe (B82 (3dSfI (B2002 (3GdNGU HMeGjI Mbhb GdedcjI GdacQjI(B: (3h gd jJfGSH gPG GdJYQja eY GdeSJLOGJ h GdJWhQGJ GdEYdGejI GdcKjQI GdJi WQCJ Ydi GdSGMI GdEYdGejI(B: (3h GSJJHY Pdc EYWGA fXQI YGeI h SQjYI Ydi GdfXGe GdbGfhfi dgPg GdgjFGJ(B: (3eY HjGf VhGHW eTQhYjI YedgG(B: (3h eG gh OhQ CNdGbjGJ GdTQa GdEYdGei h ehGKjbg ai gPG GdTCf(B: (3h Pdc ai aUd JegjOi(B. (3Ke JYQVJ GdQSGdI ai HGHgG GdChd Edi GdJRGeGJ gjFGJ GdEPGYI GdeQJHWI HeeGQSI CYeGdgG(B: (3GdJi jLH Cf JdJRe HgG ai GdeMJhi GdPi JbOeg(B: (3h bO bSeJ gPg GdGdJRGeGJ Edi eG gh NGU HGdCaQGO(B: (3h GdJRGeGJ JLGg GdOhdI(B: (3HMjK EPG CNdJ gjFGJ GdEPGYI HEMOi gPg GdGdJRGeGJ(B: (3efJgckI MkbG ef Mbhb GdCaQGO Ch CSGAJ Edi GdOhdI Jbhe eSFhdjJgG(B. (3h JfGhd GdHGH GdKGfi CMcGe GdeSFhdjI GdeOfjI GdfGTFI Yf CYeGd gjFGJ GdEPGYI(B: (3h ef NdGdg oNUU GdaUd GdChd dHjGf GdWHjYI GdbGfhfjI ddeSFhdjI GdeOfjI Yf CYeGd GdgjFGJ h CQcGfgG(B: (3HjfeG YGdL GdaUd GdKGfi BKGQ GdeSFhdjI h BdjGJ GdJYhjV YfgG(B: (3h CNjkQG MGdGJ YOe bjGe eSFhdjI GdgjFGJ Yf CYeGdgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2020s
(3HHdjhLQGajG(B: (3UaMGJ (B629-662s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3GdfXGe GdbGfhfj dgjFGJ GdGPGYIs; (3GdGWGQ GdbGfhfj ddfTGW GdGYdGejs; (3GdJRGeGJ gjFGJ GdGPGYI JLGg GdGaQGO hGdOhdIs; (3GdeSFhdjI GdeOfjI GdfGTFI Yf GYeGd gjFGJ GdGPGYIs; (3GdJYhjV hGMcGegs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs